2017
DOI: 10.7150/thno.21707
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Kernel-Reconstituted Lipoprotein Biomimetic Nanovehicles Enable Efficient Targeting “Trojan Horse” Delivery of STAT3-Decoy Oligonucleotide for Overcoming TRAIL Resistance

Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) can selectively induce apoptosis in a variety of tumor cells, but not most normal cells. Nevertheless, its therapeutic potential is limited due to the frequent occurrence of resistance in tumor cells, especially hepatocellular carcinoma cell lines. Therefore, we investigated the reversal effect of STAT3-decoy oligonucleotides (ODNs) on TRAIL resistance. Methods. Considering that the drawback of poor cellular permeability and rapid degradation in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…designed a calcium phosphate‐cored low‐density lipoprotein nanovehicle as a Trojan horse to load STAT3 decoy ODNs to overcome tumor necrosis factor‐related apoptosis‐inducing ligand resistance. 330 Wu et al. introduced PEGylated liposomal FLLL32, a specific STAT3 inhibitor that binds to the SH2 domain.…”
Section: Stat3 As a Therapeutic Target In Cancer Treatmentmentioning
confidence: 99%
“…designed a calcium phosphate‐cored low‐density lipoprotein nanovehicle as a Trojan horse to load STAT3 decoy ODNs to overcome tumor necrosis factor‐related apoptosis‐inducing ligand resistance. 330 Wu et al. introduced PEGylated liposomal FLLL32, a specific STAT3 inhibitor that binds to the SH2 domain.…”
Section: Stat3 As a Therapeutic Target In Cancer Treatmentmentioning
confidence: 99%
“…LDL-loaded drug conjugates could traffic into the cell through LDL-r mediated endocytosis similar to native LDL. Particularly, LDL-r is abundant in hepatic cells as well as they are upregulated on tumor cell membranes [ 4 , 6 , 26 , 27 ]. Additionally, nanostructure features, biodegradability, and biocompatibility of LDL particulates inhibit their clearance by the mononuclear phagocyte system [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, LDL-r is abundant in hepatic cells as well as they are upregulated on tumor cell membranes [ 4 , 6 , 26 , 27 ]. Additionally, nanostructure features, biodegradability, and biocompatibility of LDL particulates inhibit their clearance by the mononuclear phagocyte system [ 26 , 27 ]. In this study, 5-FUC was encapsulated into liposomes and LDL as a promising approach to target 5- FU into liver tissues in a selective manner.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have indicated that the sustained activation of STAT3 has a close relationship with the occurrence and development of various tumors such as gastric, esophageal, breast, and liver cancer (8). Blocking the continuous activation of STAT3 has been considered to be an effective treatment, and STAT3 decoy ODN is a continuously mature blocking method that can weaken downstream biochemical reactions by downregulating the hyperphosphorylation of intracellular STAT3 protein to inhibit the proliferation activity of tumor cells (9,10). Therefore, the competitive blocking method of inhibiting tumor proliferation through the transfection of STAT3 decoy ODN has been highly valued.…”
Section: Discussionmentioning
confidence: 99%